Pengaruh Substitusi Terigu dengan Tepung Talas Beneng (Xanthosoma Undipes K. Koch) Sebagai Bahan Pengisi Terhadap Karakteristik Nugget Ayam - Utomo, Najmia Ulil Amriyati; Putra, I Nengah Kencana; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Nugget production requires a filler. The filler most often used in chicken nugget production is wheat flour. Wheat flour is an imported foodstuff, so domestic demand for wheat flour depends on wheat flour- producing countries. On the other hand, there are several types of local flour in Indonesia that can be used to replace wheat flour, notably Talas Beneng flour. The purpose of this study is to determine the impact of replacing wheat flour with Talas Beneng flour on the characteristics of chicken nuggets, and to create the best possible chicken nuggets. A completely randomized design was employed in this study, with the treatment of wheat flour replacement by Talas Beneng flour comprising 6 levels of treatment, namely: 100%:0%; 80%:20%; 60%:40%; 40%:60%; 20%:80%; 0%:100%. Parameters observed were crude fiber content, protein content, water content, water holding capacity, cooking loss, hardness and sensory analysis, including color, aroma, texture, taste and overall acceptability. The data obtained were tested using analysis of variance (? = 0.05) and, where a significantt effect was observed, it was followed up using Duncan's multiscale test (? = 0.05). The results showed that replacing wheat flour with Talas Beneng flour had a significant effect on water content, protein content, crude fiber content, water-holding capacity, loss on cooking, hardness, color, texture, taste and overall acceptability, but no significant effect on the taste of chicken nuggets. The best nuggets were obtained when treated with a 40% substitution of Talas-Beneng flour, with the following characteristics: crude fiber content 6.10%; protein content 28.37%; water content 49.93%; water retention 17.75%; cooking loss 10.77%; hardness 5.09 N; color is like, aroma, texture, taste and general acceptability are slightly like.